Potensi Biomassa Pohon dan Emisi Karbondioksida Untuk Menilai Keseimbangan Karbon di Lingkungan - Endah Tri Wahyuningsih; Bhakti Karyadi; Rendy Wikrama Wardana; Euis Nursa’adah; Afrizal Mayub (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze carbon emissions from motor vehicles and the potential for carbon absorption by vegetation on four main roads in Bengkulu City: Padang Jati, Hibrida, Pagar Dewa, and Sukarami. The approach used is quantitative-descriptive, with data collected through traffic surveys and direct measurements of vegetation parameters during the observation period. Emissions are calculated using emission factors based on IPCC/KLHK standards according to vehicle type, while tree biomass is analyzed using allometric equations based on trunk diameter, track length, and vegetation type. Carbon analysis on four roads in Bengkulu City shows a significant imbalance between vehicle emissions and vegetation absorption. Sukarami recorded the highest emissions (751,813 kg CO₂) with a biomass of only 24,053 kg (absorption of 40,607 kg), making it a carbon source. Conversely, Padang Jati had the largest biomass (881,578 kg) compared to emissions of 431,889 kg CO₂, making it a carbon sink with absorption of 344%. Hibrida and Pagar Dewa showed intermediate conditions, with emissions of 424,145–570,063 kg CO₂ and absorption of 544,349–947 kg, indicating an unbalanced absorption capacity. These results emphasize the need to increase vegetation cover and manage green spaces as strategies for mitigating urban climate change.